2017
DOI: 10.1038/s41598-017-16740-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton communities determine the spatio-temporal heterogeneity of alkaline phosphatase activity: evidence from a tributary of the Three Gorges Reservoir

Abstract: In order to reveal the role of phytoplankton in the spatio-temporal distribution of alkaline phosphatase activity (APA), monthly investigations were conducted in the Xiaojiang River, a tributary of the Three Gorges Reservoir in China. Different APA fractions, environmental parameters, and phytoplankton communities were followed. High spatio-temporal variations of APA were observed, with the highest value in summer and the lowest in winter. The annual average APAT (total alkaline phosphatase activity) ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This unique property is associated with changes in water quality. For example, alkaline phosphatase positively correlated with turbidity, chemical oxygen demand, and chlorophyll a (Yuan et al, 2017), meaning that regions with high disturbance may have higher phosphatase activity. Our data confirm this hypothesis, and show that phosphatase activity was highest in High Agriculture/Industry region (see Table S12).…”
Section: Discussionmentioning
confidence: 99%
“…This unique property is associated with changes in water quality. For example, alkaline phosphatase positively correlated with turbidity, chemical oxygen demand, and chlorophyll a (Yuan et al, 2017), meaning that regions with high disturbance may have higher phosphatase activity. Our data confirm this hypothesis, and show that phosphatase activity was highest in High Agriculture/Industry region (see Table S12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that other limitations, like N (Kuenzler and Perras, 1965) or Si (Fuentes et al, 2014), can lead to an increase in APA. Changes in the community structure may also influence APA (Lin et al, 2015;Yuan et al, 2017). The observed differences in the picoeukaryote community under P replete conditions could alter nutrient uptake behaviour because picoeukaryotes are known to be very efficient in assimilating phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of 2 mL culture in a 15-mL PP tube was mixed with 1 mL 0.5 M Tris-HCl buffer pH 8 and 2 mL 0.3 mM p-nitrophenyl phosphate, incubated for 4 h at 37 o C and then mixed with 0.1 mL 0.1 M NaOH. Subsequently, the sample was filtered with Whatman paper number 42 (Whatman, Jakarta, Indonesia) of known weight and used for alkaline phosphatase activity analysis following the modified method of Ihlenfeldt and Gibson (1975) and Yuan et al (2017), with a 4-nitrophenol standard curve. Activity was expressed as nmol/min/g ww.…”
Section: Determining Alkaline Phosphatase Activitymentioning
confidence: 99%